Track distributions on LR-115 detector for radon measurements using diffusion chambers - Palacios, Daniel; Sajo Bohus, Laselo; Viloria, Tony (Ciencia, 1970)
Analytic calculations and Monte Carlo simulations of track distributions induced by radon and its alpha emitter daughters, for different chamber geometries and critical incidence angles, were carried out. It was assumed uniform distribution of 222Rn and its daughters in chamber volume and inner wall, respectively. By both methods similar results were obtained. It was determined that, in dependence of chamber diameter, uniform and non-uniform track distributions will take place in detector. Two types of non-uniform distributions can be presented: higher track concentration toward the central area of the detector or the opposite, with higher concentration near the borders. Alpha particle emissions occurring in effective volume or effective surface lead to non-uniform track distributions with errors in track density calculation higher than 30%. Optimum diameters for higher density and more uniform distribution of tracks were determined. The influence of non-uniform distribution of radon daughters in chamber wall on track density and its distribution is discussed.